On functionally-graded crashworthy shape of conical structures for multiple load cases - Pang, Tong; Li, Yinfeng; Kang, Hehe; Sun, Guangyong; Fang, Jianguang; Li, Qing (Journal of mechanical science and technology, 2017)
Many studies on energy absorbers have been focused on tapered tubes because they have significant advantages in crashworthiness and provide a desired constant load-deflection response. However, few studies have been reported on tapered tubes with nonlinearlyvariable diameters along the longitudinal direction. This paper presents thin-walled Functionally graded tapered tube (FGTT) with a diameter varying nonlinearly subject to axial (0°) and oblique (10°, 20°, 30°) impacts. To explore the advantages of FGTT, conventional Straight/Conical circular tube (SCT/CCT) with the same mass are compared; and FGTTs with a gradient exponent n > 1 are found to be preferable to others in terms of energy absorption capacity under small impact angles. Then, crashworthiness analyses of different crushing distances are conducted and it is found that under a large impact angle (e.g. 20°, 30°), FGTT with a short crushing distance (e.g. 40 mm) have a higher mean crashing force than long crushing distance (e.g. 120 mm), especially for n > 1. In addition, the effect of geometric parameters, such as the gradient exponent n and diameter range Δ D between top (incident) and bottom (distal) diameters of FGTTs, are also studied and it is found that the FGTT with Δ D = 40 mm and n > 1 exhibits better crashworthiness than the others under small impact angles (0°, 10°). This paper demonstrates that such FGTT structures have a certain potential to be an energy absorber.